A dívida dos municípios paraenses que aderiram à municipalização do ensino e a norma constitucional permissiva de retenção de verbas transferidas: um estudo de caso sobre o estado do Pará - LOBÃO, Simone Ferreira (Universidade Federal do Pará, 2017)
This dissertation will look into the conditions of the municipalities of the State of Pará, that have adhered the municipalization of the education in the 90‘s, which have ceased conveying the payers‘ financing contributions to the government of the State, which have churned up a considerable debit before the State Financing Security Fund. It is about a complexity of the Brazilian federalism, yet to be sorted out, which is, therefore, worth being examined. Thus, the general goal of this research is based on the norm extracted from the Art. 160, a unique paragraph of the Federal Constitution – presenting some changes in the Constitutional Amendments (03/93) and (29/00) – authorizing the retention, by the State, of the reasonable values to the Municipalities, caused by the State tax-collection participation, in case of a municipal debit existence. This study was conducted by two leading up questions. First, it consisted in analyzing whether the municipalities were reliable to develop the public policies upon their material competence, independently of the money, transferred by the Union and the State. In parallel, the second investigating inquiry would be whether the collection through retention would reflect on the fundamental rights of the population, under the municipal power. On the face of these inquiries, as it is the first assumption of this dissertation, brought in the presentation of this research-project, I have affirmed that the autonomy maintenance of the State of Pará‘s municipalities would be unviable just with its own tributes collection. And the second assumption consisted in the affirmation that, in case of the implementation of retention, the municipal debtor would have a great impact on the budget, thus bringing about a hefty difficulty in the public policies concretion, related to the human rights, on the verge of being restrained. I have therefore pondered upon the offensive fundamental rights order, the municipal autonomy and, therefore, the federative alliance itself. In the purpose of analyzing the fullness of such assumptions, this dissertation was broken into three chapters. The first chapter was dedicated to the essential concepts of the academic work development, as the difference between the positive law language and the science of Law language; between the norm and norm texts; the concept of juridical norm; its classification between conduct and structure norms; as well as general, abstract, individual and concrete norms. Moreover, I shall present the model of rules and principles as normative species, beyond the conception of the juridical system. The second chapter is conveyed to the study of federalism and the Brazilian political entities financing system and its importance to the human rights concretion. In the third and last chapter, I shall specifically discuss about the debt of the municipalities which have adhered the municipalization of the education: from the analysis of a great debtor.